2014
DOI: 10.17221/43/2014-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Stand-replacing disturbance does not directly alter the succession of Norway spruce regeneration on dead wood

Abstract: Density of regeneration in European subalpine Norway spruce (Picea abies) forests is typically low with regeneration primarily located on dead or decaying wood. The post-disturbance development of this regeneration is crucial for natural forest succession. The aim was to identify the influence of disturbance on regeneration on decaying logs immediately after a severe disturbance event. Study plots were established in two subalpine spruce forests: the first, an undisturbed site located in the Hrubý Jeseník Mts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…We found recently germinated seedlings on plots of all decay stages, starting with stage 2 since no stems of decay stage 1 were present at the time of sampling.Červenka et al [52] found a tendency of regeneration with heights of 0-5 cm to establish on little decayed and less occupied logs over a three-year observation period. Takahashi et al [53], distinguishing between five decay stages, also reported the presence of Picea jezoensis and Picea glehnii regeneration on logs of decay stage 2.…”
Section: Factors With a Significant Effect On Seedling Densitymentioning
confidence: 98%
“…We found recently germinated seedlings on plots of all decay stages, starting with stage 2 since no stems of decay stage 1 were present at the time of sampling.Červenka et al [52] found a tendency of regeneration with heights of 0-5 cm to establish on little decayed and less occupied logs over a three-year observation period. Takahashi et al [53], distinguishing between five decay stages, also reported the presence of Picea jezoensis and Picea glehnii regeneration on logs of decay stage 2.…”
Section: Factors With a Significant Effect On Seedling Densitymentioning
confidence: 98%
“…Son yıllarda hızla artan dünya nüfusunun kentleşmenin de daha hızlı bir şekilde gelişmesine sebep olmuştur (Akseki ve Meşhur, 2013). İnsan aktivitelerinin ve yanlış müdahalelerin doğal doku üzerindeki tahribatları büyük ölçülerde olabilmektedir (Bruna et al, 2013;Janda et al, 2014;Cervenka et al, 2014). Arazi örtüsünde ve doğal dokuda meydana gelen değişimler doğrudan ekosistemleri etkilediği için son zamanlarda önemli konulardan biri haline gelmiştir (Foley et al, 2005;Verburg et al, 2009).…”
Section: Sonuçunclassified
“…The important role of deadwood for the diversity maintenance of different organisms-fungi [12][13][14], invertebrates [15,16], mosses, and lichens [5,13,[17][18][19], as well as vascular plants [9,[20][21][22][23][24][25]-have been shown in numerous studies. Lying deadwood is an essential substrate for the natural regeneration of some tree species [26][27][28][29][30][31][32][33][34]. The possible advantages of a woody substrate are constant humidity [4,29,34], smoothed temperature regime, greater mineral nutrition availability [35], as well as the absence of root competition between the tree layer [4] and the ground cover [36].…”
Section: Introductionmentioning
confidence: 99%